Hubungan Obesitas dengan Perubahan Perilaku pada Remaja di SMPN 4 Bandar Lampung - Putri Giani Purnamasari; Khairun Nisa Berawi; Fitria Saftarina (CV. Jasa Sukses Abadi, 2020)
Obesity (overweight) is a fundamental disease from non-communicable diseases such as diabetes, hypertension, and cardiovascular disease who still becomes a major health issue in Indonesia and the world. The teenager is a transition period that involves changes in physiological, psychological, social, and can develop into overweight or obesity. The fear of being obese is more common in girls than boys, and this explains why an effort to lose weight is mostly found in girls. This study aimed to determine the relationship between obesity and teenagers' behavioral changes in 14-16 years old of SMPN 4 Bandar Lampung students. It was a comparative analytic with a cross-sectional study. The sampling method used a case-control and using a questionnaire as a measuring tool. Data were then analyzed with a chi-square test. The study was conducted against 77 respondents with 48 respondents (62.3%) who were obese and 29 respondents (37.7%) not obese. While as many as 20 respondents (26.0%) had problematic behavior and 57 respondents (74.0%) did not have problematic behavior. The result of the chi-square test with a p-value was 0.015. There was a significant association between obesity with the teenager's behavior change in SMP Negeri 4 Bandar Lampung.